A phonetic study of Zootopia characters’ voices in Brazilian Portuguese dubbing: the role of stereotypes - Crochiquia, Alice; Eriksson, Anders; Fontes, Mario A.S.; Madureira, Sandra (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
This work comprises an experimental investigation approach of expressive speech that integrates methodological procedures of perceptual and acoustic analyses. As the object of this work, we have focused on voice quality and vocal dynamics. Speech samples from the four main personality-distinct characters in the animated feature fi lm “Zootopia” dubbed by Brazilian voice actors have been analysed. Due to the expressive function of voice quality, we have posed the following question: what types of voice quality and vocal dynamics settings were used by the voice actors in the Brazilian dubbing of “Zootopia” to compose the vocal profi les of the characters? Perceptual evaluation of the 54 speech stimuli was performed using the Vocal Profi le Analysis protocol (Laver & Mackenzie Beck, 2007). Acoustic measures were automatically extracted using the ExpressionEvaluator script (Barbosa, 2008) for PRAAT. The profi les for each of the four characters were composed based on the psychological traits described in the fi lm script. The results of the acoustic analysis, the perceptual analysis of voice quality and vocal dynamics settings were correlated using the MFA (Multiple Factor Analysis) method in the R environment based on 40 variables (quantitative and qualitative) and it turned out that the speech stimuli were distributed in 6 clusters according to the variables analysed. The quantitative variables that presented the highest correlation percentage were: Standard Deviation of f0 Derivative, Standard Deviation of Spectral Tilt, f0 Median. The qualitative variables that presented the highest correlation percentage were: Lowered Larynx, Lip Rounding, Breathy Voice and Minimised Pitch Range. The research has presented evidence in favor of the symbolic use of phonic matter and contributions to the understanding of how vocal stereotypes are established.